2021
DOI: 10.1101/2021.03.19.21253980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Thrombotic Adverse Reactions of COVID-19 AstraZeneca Vaccine reported to EudraVigilance database

Abstract: The development of safe, effective, affordable vaccines against COVID-19 remains the cornerstone to mitigating this pandemic. Early December 2020, multiple research groups had designed potential vaccines. From 11 March 2021, several European countries temporarily suspended the use of the Oxford-AstraZeneca vaccine amid reports of blood clot events and death of a vaccinated person, despite the European Medicines Agency and the World Health Organization assurance that there was no indication that vaccination was… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
0
18
1
1
Order By: Relevance
“…There had been no reported anaphylactic reactions among AstraZeneca Oxford COVID-19 vaccine recipients (Moghimi, 2021). Previous studies had shown the occurrence of anaphylactic reactions after AstraZeneca COVID-19 vaccine and one study reported thrombotic events at the time when 17 million people were vaccinated (Tobaiqy et al, 2021). There are several limitations of the current study.…”
Section: Discussionmentioning
confidence: 73%
“…There had been no reported anaphylactic reactions among AstraZeneca Oxford COVID-19 vaccine recipients (Moghimi, 2021). Previous studies had shown the occurrence of anaphylactic reactions after AstraZeneca COVID-19 vaccine and one study reported thrombotic events at the time when 17 million people were vaccinated (Tobaiqy et al, 2021). There are several limitations of the current study.…”
Section: Discussionmentioning
confidence: 73%
“…We hypothesized that ChAdOx1 nCoV-19 vaccine induces a proinflammatory "danger signal" that promotes pathologic anti-PF4 antibody production in autoimmune HIT and possibly in VITT. 25,26 Accordingly, we sought to characterize the vaccine composition. Unexpectedly, we found 70-80 µg protein/mL in four independent ChAdOx1 nCoV-19 vaccine lots analyzed.…”
Section: Chadox1 Ncov-19 Vaccination-induced Inflammatory Reactions In Mice and Humansmentioning
confidence: 99%
“…7 Safety reports of COVID-19 vaccines demonstrated in previous studies are summarized in Table 1. 7,10,11,[30][31][32][33]…”
Section: Adverse Reactions After Vaccinationmentioning
confidence: 99%
“…Interestingly, unlike the mRNA vaccine, the presence of systemic adverse reactions after the second dose did not occur at a higher proportion than that after the first dose. 10,11,32 Another study reported the prophylactic effect of paracetamol on adverse reactions. 33 Although solicited local and systemic adverse reactions were more common in the ChAdOx1 nCoV-19 group than in the control group, prophylactic paracetamol reduced the frequency of adverse reactions, including pain, fever, chills, headache, and malaise.…”
Section: Reported Safety Of Chadox Ncov-19 Vaccines and The Associated Adverse Reactions After Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation